Public subsidies and cooperation in research and development: Evidence from the lab - Antonio Acconcia; Sergio Beraldo; Carlo Capuano; Marco Stimolo (Economics and Econometrics Research Institute (EERI), 2022)
We implement an experimental design based on a duopoly game in which subjects choose whether to cooperate in Research and Development (R&D) activities. We first conduct six experimental markets that differ in both the levels of knowledge spillovers and the intensity of competition. Consistently with the theory, we find that the probability of cooperation increases in the level of spillovers and decreases in that of market competition. We then replicate the experimental markets by providing subsidies to subjects who cooperate. Subsidies relevantly increase the probability of cooperation in focus markets, causing, however, a sensible reduction of R&D investments. Overall, our evidence suggests that, depending on the characteristics of the market, the use of public subsidies might be redundant, for firms would anyway joined their R&D efforts; or counterproductive, inducing firms to significantly reduce R&D investments compared to the non-cooperative scenario.
Keywords: L24; O3; 330; Cooperation in R&D; Public subsidies; knowledge spillovers; market competition